Manufacture of melamine urea formaldehyde particleboard from hujan panas (croton argyratus) / Jamaludin Kasim ... [et al.] - Kasim, Jamaludin; Yamani, Shaikh Abdul Karim; Ahmad, Abdul Jalil; Basir, Saimin; Salleh, Jalali (Universiti Teknologi MARA Cawangan Pahang, 2001)
Croton argyratus locally known as hujan panas was used in the Manufacture of melamine urea-formaldehyde and cement bonded particleboard. It has an average specific gravity 700 kgm-3 and the high holocellulose content indicates its potential as a raw material for board manufacture. Single-layer particleboard with a resin content of 6 to 10% (with 1% wax addition) was able to meet all the minimum requirements of the BS 5669 British Standards for particleboard. Three-layer boards were also able to surpass the requirements.